How to have better strategy conversations about monetizing data - Wixom, Barbara H.; Beath, Cynthia Mathis 1944-; Owens, Leslie 1972- (MIT Sloan Management Review, 2023)
Many organizations fail to make good decisions about their data monetization strategies because their leaders lack a shared understanding of how to discuss them. This confusion can impede efforts to derive more value from the company's data assets through improvements or innovation. This article shares a simple, practical matrix approach that can help remove friction from discussions about monetizing data and identify areas of business opportunity, now and in the future.